The role of micro-ribonucleic acids in normal hematopoiesis and leukemic T-lymphogenesis - S.N. Slavov (Brazilian Journal of Medical and Biological Research, 2010)
Micro-ribonucleic acids (microRNAs) are small molecules containing 20-23 nucleotides. Despite their small size, it is likely that almost every cellular process is regulated by them. Moreover, aberrant microRNA expression has been involved in the development of various diseases, including cancer. Although many data are available about the role of microRNAs in various lymphoproliferative disorders, their impact on the development of acute lymphoblastic leukemia of T-cell progenitors is largely unknown. In this review, we present recent information about how specific microRNAs are expressed and regulated during malignant T-lymphopoiesis and about their role during normal hematopoiesis.